Comparison of the Safety and Efficacy of Thermocautery-Assisted Circumcision and Conventional Surgical Circumcision - Demirhan Örsan Demir; Salih Bürlükkara; Ali Kaan Yıldız (Archives of Basic and Clinical Research)
Objective: The aim of our study was to compare the short- and long-term efficacy and safety of thermocautery-assisted circumcision and conventional surgical circumcision.